FAKTOR PENYEBAB REMAJA PUTUS SEKOLAH (Studi di Desa Koto Gunung Kecamatan Batang Kapas Kabupaten Pesisir Selatan) - Deswita, Sriwahyuni; Kasih, Fitria; Gusneli, Gusneli (Bimbingan dan Konseling, 2014)
The background of this reserach is teenagers that break from the school, and there are teenagers which decide to stop from the school before they pass it. The purpose of this research is to describe internal and external factors that cause teenagers break the school. This research is done with Qualitative Aprroach that is Descriptive Characteristic. Informants of the research are breaking teenagers, parents and friends. The data is collected toward interview. Determining informants are done using Snow Ball Procedure which informants are known from research subject with determining key informants. The result of the research explains that: 1). Internal factors cause teenagers breaking from the school such as: a). Wanted from theirself to get low education. b). Doubt with their ability. c). The school is assumpted that is not interesting, because there are assignment and role from the school. d). Learning ability is low level. 2). External factors cause teenagers breaking the school alike: a). Economic of family is so difficult. b). least attention from parents. c). Playing field or friends. d). Roles and dicipline from school make teenagers are confusing and decide to stop going school.